Imprecision in Strategic Management: an Approach Based on Complex Thinking - Weber, Wilson; Pólo, Edison Fernandes (Review of Business Management, 2007)
Strategic management is a demanding task concerning flexibility, multi-skills and perception of the environmental changes. While searching for better ways and practices, managers often face challenging situations that cannot be easily and entirely perceived and understood. They deal with facts, rumors, unpredictable situations and, many times, with the unknown. The more complex and dynamic their environment, the more difficult it gets to perform their tasks. Under some circumstances, even consolidated models can be insufficient to guarantee the success of the decisions made. Aiming to contribute to the understanding of the reasons why sometimes results are different from those expected, several aspects of systems theory, complex thinking and uncertainty were included in this paper. We hope it can be useful to explain the reasons why even reliable assumptions and solid strategic processes and models, supported by consistent information system and decision-making processes may not allow managers to dominate their future. Key-words: Complex Thinking. Uncertainty. System. Strategic Management.